1976
DOI: 10.1159/000214139
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Dependent Influence of Acetylsalicylic Acid on Platelet Functions and Plasmatic Coagulation Factors

Abstract: Lysine salt of acetylsalicylic acid (ASA) was given to ten patients by intravenous infusion. Blood samples taken at intervals during the infusion permitted the examination of the influence of the dose of ASA on platelet functions. Aggregation was significantly reduced when 50 mg ASA had entered circulation, while a diminution of PF 3 and PF4 availability could only be demonstrated when the dose had reached 500 and 200 mg, respectively. In order to exclude a longer latency time for the diminution of PF 3 and PF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
1
1

Year Published

1979
1979
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 13 publications
0
23
1
1
Order By: Relevance
“…These effects include the dose-dependent inhibition of platelet function, 74 -78 the enhancement of fibrinolysis, 79 -81 and the suppression of plasma coagulation. [82][83][84][85] In contrast to the saturable and well-characterized (nanomolar aspirin concentration, rapid time course, physiologic conditions, and single serine modification) inhibition of COX-1 by aspirin, 86,87 the putative mechanisms underpinning the non-PG effects of aspirin on hemostasis are dose-dependent and less clearly defined. For example, the inhibition of shear-induced platelet aggregation depends on the level of aspirin provided, and enhanced fibrinolysis due to N-acetylation of lysyl residues of fibrinogen is seen in vivo with high doses of aspirin (650 mg twice daily) 79 and proceeds more rapidly in vitro under nonphysiologic alkaline conditions.…”
Section: Smentioning
confidence: 99%
“…These effects include the dose-dependent inhibition of platelet function, 74 -78 the enhancement of fibrinolysis, 79 -81 and the suppression of plasma coagulation. [82][83][84][85] In contrast to the saturable and well-characterized (nanomolar aspirin concentration, rapid time course, physiologic conditions, and single serine modification) inhibition of COX-1 by aspirin, 86,87 the putative mechanisms underpinning the non-PG effects of aspirin on hemostasis are dose-dependent and less clearly defined. For example, the inhibition of shear-induced platelet aggregation depends on the level of aspirin provided, and enhanced fibrinolysis due to N-acetylation of lysyl residues of fibrinogen is seen in vivo with high doses of aspirin (650 mg twice daily) 79 and proceeds more rapidly in vitro under nonphysiologic alkaline conditions.…”
Section: Smentioning
confidence: 99%
“…12 Randomisation to aspirin or placebo Aspirin and placebo were provided by the hospital pharmacy as identical capsules. Aspirin was given at a dose of 300 mg/ day because, at this dose or higher, studies have shown that it may inhibit shear induced platelet activation 13 and thrombin generation, 14 and exert an anti-inflammatory effect. 15 Each treatment lasted three weeks to avoid any carry over effects of aspirin.…”
Section: Study Protocolmentioning
confidence: 99%
“…This was due to results showing the inhibitory effects o f the drug on platelet aggregation and plasmatic coagulation factors (21,23,28). However, at present there is no conclusive evi dence that drugs altering platelet function, such as A SA , dipyridamole and sulfin-pyrazone, have any significant effect on posttraumatic platelet aggregate formation and its complications (17).…”
Section: Introductionmentioning
confidence: 99%